2021
DOI: 10.1177/13591053211047148
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion and sleep quality: Examining the mediating role of taking a proactive health focus and cognitive emotional regulation strategies

Abstract: Sleep quality (SQ) impacts health yet many university students get poor sleep. Self-compassion (SC)—care for oneself during challenging times—is associated with SQ yet how SC has these effects is unclear. This study cross-sectionally examined whether SC is negatively related to poor SQ and whether proactive health focus and cognitive emotional regulation strategies (CERS) mediate this relationship. University students ( N = 193) self-reported SC, proactive health focus, CERS, and SQ. SC negatively associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…Across the 20 included studies, quality ratings for Downs and Black (1998) ranged from 40% (low-quality) to 73% (moderate quality). Six studies scored within the low rating range of 40-53% (Butz & Stahlberg, 2018;Hwang et al, 2019;Li et al, 2020;Sirois et al, 2019;Vaillancourt & Wasylkiw, 2019;Wisener & Khoury, 2021) and 14 scored within the moderate quality, 60-73%, range (Butz & Stahlberg, 2018;Dunne et al, 2018;Finlay-Jones et al, 2015;Homan & Sirois, 2017;Hu et al, 2018;Miller & Strachan, 2020;Rakhimov et al, 2022;Semenchuk et al, 2021;Sirois et al, 2015Sirois et al, , 2019Wisener & Khoury, 2020. More specific study ratings can be found in Table 1.…”
Section: Quality Ratings (Downs and Black Checklist And Mediation Che...mentioning
confidence: 99%
See 4 more Smart Citations
“…Across the 20 included studies, quality ratings for Downs and Black (1998) ranged from 40% (low-quality) to 73% (moderate quality). Six studies scored within the low rating range of 40-53% (Butz & Stahlberg, 2018;Hwang et al, 2019;Li et al, 2020;Sirois et al, 2019;Vaillancourt & Wasylkiw, 2019;Wisener & Khoury, 2021) and 14 scored within the moderate quality, 60-73%, range (Butz & Stahlberg, 2018;Dunne et al, 2018;Finlay-Jones et al, 2015;Homan & Sirois, 2017;Hu et al, 2018;Miller & Strachan, 2020;Rakhimov et al, 2022;Semenchuk et al, 2021;Sirois et al, 2015Sirois et al, , 2019Wisener & Khoury, 2020. More specific study ratings can be found in Table 1.…”
Section: Quality Ratings (Downs and Black Checklist And Mediation Che...mentioning
confidence: 99%
“…Mediation checklist ratings ranged from low to high quality with scores ranging from 2 to 8 (out of 11). One study scored 8 with high quality (Study 2; Butz & Stahlberg, 2018), 12 studies scored within the moderate quality ratings within the range of 4-5 (Butz & Stahlberg, 2018;Finlay-Jones et al, 2015;Homan & Sirois, 2017;Hwang et al, 2019;Rakhimov et al, 2022;Semenchuk et al, 2021;Sirois et al, 2015Sirois et al, , 2019Wisener & Khoury, 2021), and seven scored within the low quality range of 2-3 (Dunne et al, 2018;Hu et al, 2018;Li et al, 2020;Miller & Strachan, 2020;Vaillancourt & Wasylkiw, 2019;Wisener & Khoury, 2020).…”
Section: Quality Ratings (Downs and Black Checklist And Mediation Che...mentioning
confidence: 99%
See 3 more Smart Citations